2017
DOI: 10.1080/02813432.2017.1288817
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for attending a general emergency outpatient clinic versus a regular general practitioner – a survey among immigrant and native walk-in patients in Oslo, Norway

Abstract: ObjectiveTo explore reasons for attending a general emergency outpatient clinic versus a regular general practitioner (RGP).DesignCross-sectional study using a multilingual anonymous questionnaire.SettingNative and immigrant walk-in patients attending a general emergency outpatient clinic in Oslo (Monday–Friday, 08:00–23:00) during 2 weeks in September 2009.SubjectsWe included 1022 walk-in patients: 565 native Norwegians (55%) and 457 immigrants (45%).Main outcome measuresPatients’ reasons for attending an eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…Similarly, depending on government welfare, immigrant and refugees may use ED free of charge. There were also other reasons that lead immigrants to ED such as language barriers and lack of accessing to primary care providers (15)(16)(17). Those reasons explain the high proportion of immigrant and refugees (8.7%) in frequent users in our study.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, depending on government welfare, immigrant and refugees may use ED free of charge. There were also other reasons that lead immigrants to ED such as language barriers and lack of accessing to primary care providers (15)(16)(17). Those reasons explain the high proportion of immigrant and refugees (8.7%) in frequent users in our study.…”
Section: Discussionmentioning
confidence: 74%
“…Fast track services are designed for patients seeking primary care services (often without a general practitioner) for less serious illnesses and injuries. International studies have suggested that immigrants use emergency services more for non-urgent health care problems than do native populations [ 16 , 35 , 36 ]. A Norwegian study reported that a frequent reason for not contacting a general practitioner before the emergency department was because it was difficult to access him.…”
Section: Discussionmentioning
confidence: 99%
“…Younger people, as well as non-nationals, might -on average -be less attached to their GPs or might not even have a personal GP, which leads to them seeking help at an ED rather than at GPs' practices when they need care urgently after an accident [24].…”
Section: Comparison With Related Literaturementioning
confidence: 99%